Zinc Oxide Nanoparticles Affect Biomass Accumulation and Photosynthesis in Arabidopsis - Wang, Xiaoping; Yang, Xiyu; Chen, Siyu; Li, Qianqian; Wang, Wei; Hou, Chunjiang; Gao, Xiao; Wang, Li; Wang, Shucai (Frontiers in Plant Science, 2016)
Dramatic increase in the use of nanoparticles (NPs) in a variety of applications greatly increased the likelihood of the release of NPs into the environment. Zinc oxide nanoparticles (ZnO NPs) are among the most commonly used NPs, and it has been shown that ZnO NPs were harmful to several different plants. We report here the effects of ZnO NPs exposure on biomass accumulation and photosynthesis in Arabidopsis. We found that 200 and 300 mg/L ZnO NPs treatments reduced Arabidopsis growth by ~20% and 80%, respectively, in comparison to the control. Pigments measurement showed Chlorophyll a and b contents were reduced more than 50%, whereas carotenoid contents remain largely unaffected in 300 mg/L ZnO NPs treated Arabidopsis plants. Consistent with this, net rate of photosynthesis, leaf stomatal conductance, intercellular CO2 concentration and transpiration rate were all reduced more than 50% in 300 mg/L ZnO NPs treated plants. Quantitative RT-PCR results showed that expression levels of chlorophyll synthesis genes including CHLOROPHYLL A OXYGENASE (CAO), CHLOROPHYLL SYNTHASE (CHLG), COPPER RESPONSE DEFECT 1 (CRD1), MAGNESIUM-PROTOPORPHYRIN IX METHYLTRANSFERASE (CHLM) and MG-CHELATASE SUBUNIT D (CHLD), and photosystem structure gene PHOTOSYSTEM I SUBUNIT D-2 (PSAD2), PHOTOSYSTEM I SUBUNIT E-2 (PSAE2), PHOTOSYSTEM I SUBUNIT K (PSAK) and PHOTOSYSTEM I SUBUNIT K (PSAN) were reduced about 5-fold in 300 mg/L ZnO NPs treated plants. On the other hand, elevated expression, though to different degrees, of several carotenoids synthesis genes including GERANYLGERANYL PYROPHOSPHATE SYNTHASE 6 (GGPS6), PHYTOENE SYNTHASE (PSY) PHYTOENE DESATURASE (PDS), and ZETA-CAROTENE DESATURASE (ZDS) were observed in ZnO NPs treated plants. Taken together, these results suggest that toxicity effects of ZnO NPs observed in Arabidopsis was likely due to the inhibition of the expression of chlorophyll synthesis genes and photosystem structure genes, which results in the inhibition of chlorophylls biosynthesis, leading to the reduce in photosynthesis efficiency in the plants.